Practical Ruby Projects: Ideas for the Eclectic Programmer - Cyll, Topher (Apress, 2012)
This book is titled Practical Ruby Projects. And let me start by saying that the projects are practical. But they might not be quite what you’re used to. Flip through the book. You won’t find any references to enterprise deployment. Not a word about business logic. In fact, hard as it is to believe, there’s no web programming! But if you exclude those things, what’s left? Why, everything else, of course! Each chapter in this book turns Ruby loose on a new interesting problem or project. They range from creative endeavors to investigative simulations to the exploration of computer programming languages themselves. Ruby is a programming language, but it’s also a tool to create, understand, and entertain. This book is all about Ruby.4